Leading with the (recently) successful? Performance visibility and the evolution of risk taking - Sönke Ehret; Sonja Vogt; Andreas Hefti; Charles Efferson (University of Zurich, Department of Economics, 2021)
The popular practice of 'leading by the successful' is viewed as a hallmark of motivational leadership. A central rationale for leaders to make successful team members salient is that it may induce social learning, where followers strive to adopt a favorable behavior. The reliance of a leader on such success-biased social learning presumes that imitation by followers occurs only to the extent as outstanding success was caused by a superior ability or knowledge of the respective peer. In this article, we conduct a laboratory experiment to study whether imitation of the successful may occur even if imitation necessarily fails to be an effective way of improving one's performance. The experimental approach establishes the necessary control to assure that success-biased learning cannot systematically improve the decisions made, and allows us to isolate the behavior of the followers from possible feedback effects of the leader. The data show that a substantial amount of imitation occurs, which in our setting leads to a sizeable and persistent increase of the average risk taken in the teams. Our finding thus indicates a limitation of the practice to lead with the successful.
Keywords: C91; C92; D91; 330; Social learning; laboratory experiments; motivational leadership